An Exhaustive Meta-analytical Study of the History, Evolution and Development of ‘Saraiki NLP’ - Saini, Jatinderkumar R. (INFOCOMP Journal of Computer Science, 2018)
The paper is first formal attempt worldwide to present a 200 years based chronicle of Natural Language Processing (NLP) research activities in resource-scarce Saraiki language. It presents a single major bibliography till-date comprising of nearly 100 research instances of ‘NLP of Saraiki Language’ or ‘Saraiki NLP’ (the terms used first time in research community). The listed Saraiki NLP research instances are classified in one of six proposed categories for Corpus Development, Evolution, Machine Translation System, Phonetics, Script and Social-Science. State-of-art of Saraiki NLP sub-domains along with recommendations for potential sub-domains is presented. As a best attempt exhaustive annotated and classified bibliography of Saraiki NLP, the paper is intended to be a stepping-stone one-stop resource for future Saraiki NLP research activities.